2023
DOI: 10.1002/anie.202312076
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Co‐Reduction of N2 and CO2 with CeO2 Catalyst for Urea Synthesis

Shuyi Yang,
Wensheng Zhang,
Guoliang Pan
et al.

Abstract: The effective conversion of carbon dioxide (CO2) and nitrogen (N2) into urea by photocatalytic reaction under mild conditions is considered to be a more environmentally friendly and promising alternative strategies. However, the weak adsorption and activation ability of inert gas on photocatalysts has become the main challenge that hinder the advancement of this technique. Herein, we have successfully established mesoporous CeO2‐x nanorods with adjustable oxygen vacancy concentration by heat treatment in Ar/H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 63 publications
(70 reference statements)
2
11
0
Order By: Relevance
“…After sulfur migration, a new peak assigned to sulfated O species appeared at 533.3 eV, resulting in a 0.2 eV shift to lower energy of O α and O β . Meanwhile, the proportion of O β significantly decreased by 38.7%, indicating that migrated S species preferred to absorb at lattice oxygen with the formation of S–O–Mn bonding . The XPS signal of Mn 2p 3/2 could be divided into three peaks at 643.2, 642.0, and 641.0 eV, assigned to the Mn 4+ , Mn 3+ , and Mn 2+ species, respectively (Figure f) .…”
Section: Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…After sulfur migration, a new peak assigned to sulfated O species appeared at 533.3 eV, resulting in a 0.2 eV shift to lower energy of O α and O β . Meanwhile, the proportion of O β significantly decreased by 38.7%, indicating that migrated S species preferred to absorb at lattice oxygen with the formation of S–O–Mn bonding . The XPS signal of Mn 2p 3/2 could be divided into three peaks at 643.2, 642.0, and 641.0 eV, assigned to the Mn 4+ , Mn 3+ , and Mn 2+ species, respectively (Figure f) .…”
Section: Results and Discussionmentioning
confidence: 97%
“…Meanwhile, the proportion of O β significantly decreased by 38.7%, indicating that migrated S species preferred to absorb at lattice oxygen with the formation of S−O−Mn bonding. 42 The XPS signal of Mn 2p 3/2 could be divided into three peaks at 643.2, 642.0, and 641.0 eV, assigned to the Mn 4+ , Mn 3+ , and Mn 2+ species, respectively (Figure 3f). 43 After reacting in sulfated MEA solution, the Mn 2p band of the catalyst showed a transformation from Mn 3+ to Mn 4+ and Mn 2+ , with the intensity of Mn 3+ decreasing by 32.5%.…”
Section: Self-structural Variations Of the Localmentioning
confidence: 99%
“…Due to the special electron acceptor properties of Fe 2+ and Ce 3+ , Fe 2+ and Ce 3+ in NiFe-LDH/CeO 2 can be inferred as dual-metal catalytic sites in EC-NITRR. , Meanwhile, N 2 -TPD spectra revealed that NiFe-LDH/CeO 2 also has excellent activation ability for nitrogen (Figure S14). Compared with CeO 2 , the NH 3 yield of Ni-LH/CeO 2 decreased, leading us to speculate that Ni 2+ is not the catalytic active site for NO 3 – . In addition, the NH 3 selectivities of CeO 2 , Fe-LH/CeO 2 , and NiFe-LDH/CeO 2 increased sequentially, which may be attributed to the strong adsorption effect of Ni 2+ and Fe 3+ on hydrogen radicals in NiFe-LDH/CeO 2 , promoting the hydrogenation reaction of intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an anion-inducing strategy, electrodeposition techniques, and solid metal reduction processes were used to design new CeO 2 photocatalysts with abundant OVs and improved photocatalytic performance. In various cases, as depicted in Figure a, OV defects at increasing concentrations in photocatalysts show a high optical absorption capacity along with a strong carrier recombination rate, hindering the transfer of the generated charge carriers and inhibiting photocatalytic activity. ,,, Therefore, an effective solution for coordinating the contradiction between the formation and transfer of photogenerated charge carriers in defect-rich semiconductors is a great challenge in achieving advanced photocatalytic materials.…”
mentioning
confidence: 99%
“…Ceria (CeO 2 ) as a star material in catalysis can release and/or store oxygen due to the valence-convertible Ce 3+ /Ce 4+ cations, thus exhibiting excellent tunable properties for OV engineering. Transition metal ion doping is a traditional method for improving the utilization of photogenerated carriers by increasing the number of OV defects in CeO 2 . Heat treatment in a reductive (H 2 , CO, etc.) or inert atmosphere (Ar, N 2 , etc.)…”
mentioning
confidence: 99%